The victory garden vegetable alphabet book - Pallotta, Jerry; Thomson, Bob.; Stewart, Edgar, 1959- (Watertown, MA : Charlesbridge, 1992)
Describes a variety of terms, from A to Z, relating to vegetable gardening, beginning with asparagus and ending with zucchetta.
Also published under title: The victory garden alphabet book.
Keywords: Vegetables; English language -- Alphabet; Vegetable gardening; Gardening; Alphabet